Environmental management in Brazilian higher education. (2019) - Engelman, Raquel; Tometich, Patrícia; Schreiber, Dusan; Nascimento, Luis Felipe; Fracasso, Edi Madalena; Figueiro, Paola Schmitt
This research aims to investigate how the higher education institutions in Brazil are dealing with environmental issues. In this sense, a study was made to identify Environmental Management practices in Brazilian higher education institutions based on a survey with 75 institutions. The results showed that 22 practices are carried out by most of the universities in the country. Institutions that prioritise environmental management, implementing Environmental Management Systems and deploying specific department for their management, have higher level of practices adoption. The results demonstrated that Brazilian institutions are oriented to comply with its environmental and social responsibility, but lack of resources (especially human and financial) and of interest of the own higher education institutions interest are some of the main barriers found. The higher education institutions organise awareness programs for employees, and environmental policies are their management priorities, being part of their strategic planning and budget forecasting.